Project 1B: Cultural collage / Anis Zulfah Zulkifli - Zulkifli, Anis Zulfah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The collage created is the appreciation and interpretation of the Iban tattooes. Every stroke, line and image of their tattoos has its own symbolic meaning. The materials used such as tree roots, compact discs, and translucant vellum papers represent the vast meanings of each Iban tattooes. Iban warrior made a promise with spirit named “Hantu Pantang” on continuing the tattoo tradition through Iban’s people generations.